The method of calculating saturated class-F amplifier - A. P. Yefymovych (Известия высших учебных заведений России: Радиоэлектроника)
The proposed method of calculating the saturated class-F amplifier. The determined values of the cut-off angles at which can be realized this amplifier. It is shown that a saturated class-F amplifier can be realized in high cut-off angle range than an unsaturated class-F amplifier.